Cavum Vergae with Transient Loss of Conciousness in a Child: A Case Report and Brief Literature Review - Uduma, FU; Adams, N (Asian Journal of Medical Sciences, 2013)
Cavum vergae is a triangular fluid filled cavity posterior to foramen of Monro. They are seen in premature and term infants up to 2 months of age. It is of little clinical significance. Our patient is a 14year old girl with cavum vergae diagnosed with brain computed tomography and magnetic resonance imaging. These investigations were sequel to episodes of headache and one hour loss of consciousness with no antecedent complaints. Since no complicating evidence of hydrocephalus was seen, she was managed symptomatically. DOI: http://dx.doi.org/10.3126/ajms.v5i1.8107 Asian Journal of Medical Science Vol.5(1) 2014 pp.73-76